PECULIARITIES OF THE BEHAVIOR OF AN ULTRATHIN LAYER OF AN EVAPORABLE LIQUID IN THE PRESENCE OF A SURFACTANT ON A FREE DEFORMABLE INTERFACE - Bratsun, D.A.; Gordeeva, V.Y.; Lyushnin, A.V. (Perm Federal Research Centre Journal, 2017)
Evaporation of a thin layer of a polar liquid (water) having a free surface and located on a solid substrate is investigated. A solvable surfactant is placed on the free liquid - vapor interface. The surface tension coefficient is a linear function of the surface concentration of the surfactant. The surface energy of the solid - liquid contact line is a nonmonotonic function of the layer thickness and is the sum of the van der Waals interaction and the specific interaction of the double electric layer on the interface. The effect of the solvable surfactant on the dynamics and stability of the evaporation front propagation in a thin liquid film is analyzed in the long-wave approximation in the system of Navier-Stokes equations.